2016
DOI: 10.1074/jbc.m116.740555
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Ethanol-induced Intoxication by a Novel Modulator of Gβγ Protein Potentiation of the Glycine Receptor

Abstract: The acute intoxicating effects of ethanol in the central nervous system result from the modulation of several molecular targets. It is widely accepted that ethanol enhances the activity of the glycine receptor (GlyR), thus enhancing inhibitory neurotransmission, leading to motor effects, sedation, and respiratory depression. We previously reported that small peptides interfered with the binding of G␤␥ to the GlyR and consequently inhibited the ethanol-induced potentiation of the receptor. Now, using virtual sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…The present data, together with a recent study that showed that a small molecule can reduce the sedative effects of ethanol (San Martin et al . ) by interfering with the GlyR‐Gβγ protein/protein interaction, support the notion that the present type of study can lead to the development of therapeutics to treat toxic and addictive ethanol behaviours.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The present data, together with a recent study that showed that a small molecule can reduce the sedative effects of ethanol (San Martin et al . ) by interfering with the GlyR‐Gβγ protein/protein interaction, support the notion that the present type of study can lead to the development of therapeutics to treat toxic and addictive ethanol behaviours.…”
Section: Discussionsupporting
confidence: 76%
“…These regions should play a role on the protein–protein interaction with Gβγ and potentially for therapeutic development (San Martin et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…For evaluation of the righting reflex, the offspring mice were placed in the supine position. When they were able to right themselves within 2 s and repeat the movement 3 times successfully, we recorded that as achievement of the righting reflex (San Martin et al, 2016). To evaluate crawling ability (Nagao, Kawachi, Kagawa, & Komada, 2014), we observed whether the offspring could crawl for a distance longer than 3 cm without rearing.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the structure Loop 2 of a glycine receptor is considered a key structure and determines sensitivity to EtOH (Crawford et al, 2007; Eggers and Berger, 2004; Perkins et al, 2012). In addition, homomeric α1 or α2 GlyRs in Xenopus oocytes may be potentiated, while the activities of GlyR can be enhanced by prolonging the burst duration by EtOH (Mascia et al, 1996; San Martin et al, 2016; Welsh et al, 2009). Furthermore, BNO and brucine antagonize the α1 and α1β glycine receptors with Ki values of 1.4 and 1.7 μmol/l, respectively, in human embryonic kidney 293 cells (Jensen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%